ANALISIS KESTABILAN LERENG TAMBANG BATUBARA BERDASARKAN LIMIT EQUILIBRIUM METHOD DAN FINITE ELEMENT METHOD DI PT. MARUNDA GRAHA MINERAL KECAMATAN LAUNG TUHUP, KABUPATEN MURUNG RAYA, PROVINSI KALIMANTAN TENGAH - Adi Saputro Adi Saputro (Retii, 2022)
Marunda Graha Mineral in open-pit coal mining is faced with two things, namely intact rock (intact rock) and rock mass (rock mass), in addition to conditions caused by changes in ground water content or runoff, causing rocks to have the potential for landslides. Analyzing slope stability or recommending geometry in this research area uses two methods, namely the Limit Equilibrum (LEM) method and the finite element method (FEM) with Mohr-Coloumb failure criteria. The overall slope safety factor is guided by the Minister of Energy and Mineral Resources Decree 1827/30/MEM/2018 with the criteria of medium landslide severity under static conditions of FK 1.3 and dynamic 1.1. The results of the analysis of a single slope with a ladder height of 8 m, a slope of 40 and the overall slope of static conditions, boundary equilibrium for simplified janbu at a height of 32 meters with an overall angle of 30.5 with a ladder height of 8 m, bench width 5.5 m, ladder angle 40 and for Spencer at a height of 32 m in the overall corner of 33.5 bench width 4 m ladder angle 40 , while for the finite element method obtained static conditions have a geometry at a height of 32 m with an overall angle of 30 bench width 5 m. Under dynamic conditions, the boundary equilibrium for a simplified janbu at a height of 32 meters with a total angle of 33˚ bench width 4 m and for spencer at a height of 32 m at a total angle of 34˚ bench width 3 m, while the finite element is obtained at a height of 32 m with a total angle of 31 with a bench width of 5 m. Analysis using two methods resulted in a difference in the value of the safety factor that did not differ much between boundary and finite element equilibrium. The safety value in the finite element method shows lower results when compared to the boundary equilibrium method. Where the difference between the security value of the simplified Janbu and the SRF is 2% - 5%, while the difference between Spencer and the SRF is 12% - 14%. This difference can be caused by differences in data input, differences in calculation iterations, and differences in the limits of each application. . Keyword : Overall slope, limit equilibrium method, finite element method, Mohr-Coulomb